2013
DOI: 10.1080/17429145.2013.850596
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide dismutase isozyme activity and antioxidant responses of hydroponically cultured Lepidium sativum L. to NaCl stress

Abstract: The present study was focused to assess the physiological behavior and antioxidant responses of the medicinal plant Lepidium sativum L. (commonly called Garden cress) subjected hydroponically to NaCl stress during its vegetative growth stage. The results showed that the addition of NaCl to growth medium significantly reduced plant growth. The magnitude of the response was also linked to the plant organ considered and NaCl concentration supplemented to the medium. Tissue hydration seemed unaffected by salinity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…This direct relationship between CAT activity and cellular peroxide level may be explained by the use of other H 2 O 2 scavenging enzymes like ascorbate peroxidase (APX) and peroxidases (POX) as the major scavenger of the hydrogen peroxide under low CAT activity (Willekens et al 1997). Moreover, maintaining cytoplasmic Ca 2+ concentrations in all varieties under moderate salinity (100 mM), and its stimulation in root under high salinity (500 mM) ( Figure 3D, (Figure 4D), suggested that Ca 2+ could be correlated with the increase of antioxidant enzyme activities and the decrease of cell membrane lipid peroxidation as previously demonstrated (Ben Amor et al 2005;Manaa et al 2014b).…”
Section: Discussionsupporting
confidence: 73%
“…This direct relationship between CAT activity and cellular peroxide level may be explained by the use of other H 2 O 2 scavenging enzymes like ascorbate peroxidase (APX) and peroxidases (POX) as the major scavenger of the hydrogen peroxide under low CAT activity (Willekens et al 1997). Moreover, maintaining cytoplasmic Ca 2+ concentrations in all varieties under moderate salinity (100 mM), and its stimulation in root under high salinity (500 mM) ( Figure 3D, (Figure 4D), suggested that Ca 2+ could be correlated with the increase of antioxidant enzyme activities and the decrease of cell membrane lipid peroxidation as previously demonstrated (Ben Amor et al 2005;Manaa et al 2014b).…”
Section: Discussionsupporting
confidence: 73%
“…Therefore, POD plays important role ROS metabolism and thus, conferred tolerant to maize seedlings under all the stresses. The induced activity of POD under salinity was reported in soybean [47], liquorice [48], and in Lepidium sativum [49], whereas drought stress-induced POD activity was also reported in rapeseed [50], rice [20][21][22], and liquorice [48]. On the other hand, enhanced POD activity under low P was also reported in rice [4].…”
Section: Discussionmentioning
confidence: 94%
“…The connection between isozyme polymorphism and an activity of antioxidant system in plants under stress conditions was shown in a few works 31 32 . It suggests that some changes observed in the antioxidant system may be due to alterations in the genetic structure of studied populations.…”
Section: Discussionmentioning
confidence: 99%